2019
DOI: 10.21608/ejhc.2019.46257
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Organizational Justice on Organizational Citizenship Behavior among Nurses

Abstract: Background: Justice and its implementation are one of the fundamental and innate needs of the human. Employees' exhibit higher levels of performance, loyalty, act more than their job descriptions and have high level of organizational citizenship behavior when they believe they are treated fairly at workplace. Aims: This study aimed to investigate the relationship between organizational justice and organizational citizenship behavior among nurses. Setting: El Demerdash university Hospital. Design: a descriptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
2
2
Order By: Relevance
“…This may be due to the different perceptions of the studied nurses about organizational justice in salary, decisions, and personal relationships from their managers. This finding is in agreement with Mohamed et al, [40] who found that the perceived level of the individuals of the sample was moderate for the organizational justice in all its dimensions. Also, Mohamed et al [41] showed that more than half of the nurses had a moderate level of perceived organizational justice.…”
Section: Discussionsupporting
confidence: 93%
“…This may be due to the different perceptions of the studied nurses about organizational justice in salary, decisions, and personal relationships from their managers. This finding is in agreement with Mohamed et al, [40] who found that the perceived level of the individuals of the sample was moderate for the organizational justice in all its dimensions. Also, Mohamed et al [41] showed that more than half of the nurses had a moderate level of perceived organizational justice.…”
Section: Discussionsupporting
confidence: 93%
“…Conversely, the present findings are in disagreement with that of Mohammed et al (28) ,who examined the influence of organizational justice on organizational citizenship behavior among nurses at El Demerdash university hospital in Egypt, that displayed high organizational citizenship behavior level. As well, Al-Ahmadi et al (29) ,who identified the level of organizational citizenship behavior and its relation to job satisfaction in the nursing field in Jeddah, Saudi Arabia, that displayed high organizational citizenship behavior level, and Mustafa et al (30) , who determined the relation among job crafting, work involvement and organizational citizenship behavior among head nurses at Zagazig university hospitals in Egypt, and reported high organizational citizenship behavior level.…”
Section: Zagazig Nursing Journalcontrasting
confidence: 99%
“…On the other hand, this result was in disagreement with some previous studies such as that was carried out by Metwally et al (25) , who reported that there was nonstatistically significance relation between personal characteristics and organizational citizenship behavior and the study done by Mohammed et al (28) , who reported that there was non-statistically significant relation between organizational citizenship behavior of the studied nurses and their personal characteristics.…”
Section: Zagazig Nursing Journalcontrasting
confidence: 98%
“…It aimed to assess organizational citizenship behavior among staff nurses. It developed by Organ, (1990), and was adopted from Mohamed, (2018). It contains of 20 items classified into five dimensions as following description:…”
Section: Second Tool: Organizational Citizenship Behavior Scalementioning
confidence: 99%
“…Study subjects had low citizenship behavior if total score was less than 60 %. While it is considered moderate if score was ranged from 60-75% and it is considered high if total score was more than 75% (Mohamed, 2018).…”
Section: Scoring Systemmentioning
confidence: 99%